Gay Male Nomenclatures: Bounding the Information Ecology of Desire and Performance in Technologies and Applications - Martínez-ávila, Daniel; Pinho, Fabio Assis; Nascimento, Francisco Arrais [UNESP]; Smiraglia, Richard P. (IMR Press, 2023)
Information technology has brought many advantages for communications and new possibilities for knowledge organization, but also many ethical challenges and risks for groups at the social margins such as the LGBTIQ+ communities. Self-identifying nomenclature from social media websites such as Grindr, XVideos, TikTok, and Scruf were gathered; keywords and phrases were extracted and arrayed by frequency distribution and compared across sites. There are obvious site-specific emphases: in XVideos the terms are more sexual, in Scruf they are more identity oriented. The aggregated data show different practices of representation of gay males reflecting their sexual and affective interests, likes, and desires. These findings reflect the act of defining and organizing the knowledge about the identity of the group based on what is desirable both in themselves and in others pertaining to the same. The resulting terms can be grouped into three classes: sexual desires/orientation desire, physical characteristics, and sexual roles or performances. In addition to gender self-denomination terms, there are terms that can represent a person’s sexuality, including the description of the romantic or sexual attraction they feel. The snapshots of representation in different social applications studied here show a classification used and shared by the gay male community at present.
Keywords: gay male community; information ecology; knowledge representation; LGBTIQ+ communities